Německá arktická politika - Nguyenová, Thi Khanh Ly (Univerzita Karlova, Fakulta sociálních věd, 2024)
The thesis deals with Germany's Arctic policy in the last decade and focuses on its security dimension. The Arctic region has undergone many changes in recent years due to climate change and the new geopolitical situation, including a change in the security situation. Based on the concepts of civilian power and securitization, the thesis examines whether Germany approaches the Arctic as a multilateral actor or whether the Arctic has gained importance in German foreign and security policy and become a recognized security issue for Germany. The introductory part of the thesis is devoted to a general introduction of the Arctic region, its definition and a presentation of the global security, environmental and economic aspects and challenges associated with it. The thesis then briefly outlines the history of German involvement in the Arctic, its activities and Germany's relevance to the region. The main research part of the thesis is divided into the bilateral and multilateral dimensions of German Arctic policy, thus reflecting the nature of German multilateralism. The results of the examination of German Arctic policy have shown that Germany is aware of the various aspects of Arctic security and its global dimension, however, the focus is on the climate and economic security issues of the region. Even. Diplomová práce se zabývá politikou Německa v oblasti Arktidy v posledním desetiletí a soustředí se na její bezpečnostní rozměr. V arktickém regionu dochází v posledních letech v důsledku klimatických změn a nové geopolitické situace k mnoha proměnám, včetně změny bezpečnostní situace. Práce vychází z konceptů civilní mocnosti a sekuritizace a zkoumá, zdali Německo přistupuje k Arktidě jako multilaterální aktér, anebo v německé zahraniční a bezpečnostní politice nabyla Arktida na významu a stala se pro Německo uznávanou bezpečnostní otázkou. Úvodní část diplomové práce se věnuje obecnému představení arktického regionu, jeho vymezení a předložení globálních bezpečnostních, environmentálních a ekonomických aspektů a ...